2000
DOI: 10.1097/00007632-200003150-00005
|View full text |Cite
|
Sign up to set email alerts
|

Increased Signal Intensity of the Spinal Cord on Magnetic Resonance Images in Cervical Compressive Myelopathy

Abstract: Increased signal intensity was not related to a poor outcome of conservative treatment or severity of myelopathy in the patients with mild cervical myelopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
85
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(93 citation statements)
references
References 15 publications
3
85
0
3
Order By: Relevance
“…Prospective studies in which patients were randomized into conservative and operative treatment groups have suggested that patients with mild CSM do not frequently progress at early time points (2-3 years) [27,28,32].…”
Section: Conservative Managementmentioning
confidence: 99%
“…Prospective studies in which patients were randomized into conservative and operative treatment groups have suggested that patients with mild CSM do not frequently progress at early time points (2-3 years) [27,28,32].…”
Section: Conservative Managementmentioning
confidence: 99%
“…The most serious complication is spinal cord compression, resulting in neural tissue damage and a syndrome of spinal cord dysfunction known as cervical spondylotic myelopathy (CSM). Magnetic resonance imaging (MRI) is the modality of choice for quantifying the extent of degenerative alterations and spinal canal narrowing, though it has been proven to have low sensitivity in myelopathy detection, ranging 15-65 % [1][2][3][4][5][6]. Abnormal T2 signal intensity of the compressed spinal cord, which is considered to reflect myelopathic changes, is not always present, even in very advanced stages of clinically evident myelopathy, and poorly correlates with disease severity [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Yapılan son çalışmalarda, servikal miyelopatinin tedavisinde, sebep ister servikal disk hernisi, ister spondiloza bağlı kanal darlığı olsun, kompresyon miyelopatisi hafif düzeyde ise, öncelikle prognostik faktörlerin belirlenmesi ve hastaların konservatif tedavi ile takip edilmesinin tedavinin daha uygun olduğu savunulmaktadır (11)(12)(13). Bizim vakamızda da servikal MRG'de miyelomalazik sinyal değişikliği olmasına rağmen belirgin nörolojik defisitin olmayışı acilen cerrahiye yönlenmeden önce prognostik faktörlerin değerlendirilmesi gerektiği sonucuna varmamıza neden olmuştur.…”
Section: Discussionunclassified